Biosensors and Bioassays Based on Lipases, Principles and Applications, a Review - Pohanka, Miroslav (Molecules (Basel, Switzerland), 2019)
Lipases are enzymes responsible for the conversion of triglycerides and other esterified substrates, they are involved in the basic metabolism of a wide number of organisms, from a simple microorganism and to mammals. They also have broad applicability in many fields from which industrial biotechnology, the production of cleaning agents, and pharmacy are the most important. The use of lipases in analytical chemistry where it can serve as a part of biosensors or bioassays is an application of growing interest and has become another important use. This review is focused on the description of lipases chemistry, their current applications and the methods for their assay measurement. Examples of bioassays and biosensors, including their physical and chemical principles, performance for specific substrates, and discussion of their relevance, are given in this work.
Keywords: ester; amperometry; Enzyme Activation; biorecognition; nanostructure; biosenzitivní techniky; lipase; Biological Assay; lipasa; biotest; Electrochemical Techniques; enzyme; hydrolýza; elektrochemické techniky; Biosensing Techniques; catalysis; nanoparticle; biosensor; Catalysis; aktivace enzymů; voltammetry; Lipase; bioassay; potentiometry; katalýza; Hydrolysis